Prophetic Leadership in Dormitory Education at the Universitas Muhammadiyah Kudus - Toni Ardi Rafsanjani; Mohamad Ali; Dewi Rohmah (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to explore the implementation of prophetic leadership by dormitory managers at the Universitas Muhammadiyah Kudus (UMKU), analyze the various challenges faced in its implementation, and evaluate its impact on the formation of student character, morals, and spirituality. Theoretical framework: This research is based on prophetic leadership theory that is rooted in prophetic values of humanization, liberation, and transcendence, and is connected to the concept of servant leadership that emphasizes service and exemplary leadership. Literature review: This study includes a study of prophetic leadership, character development theories in a dormitory education environment, as well as various previous studies on the influence of leadership on the spiritual and moral development of students. Methods: This study uses a descriptive qualitative method with data collection techniques through in-depth interviews, participatory observations, and documentation, then analyzed using a thematic approach to find relevant patterns. Results: The results show that more than 80% of students recognize the significant role of dormitory leaders in shaping their worship habits and character, although formal coaching related to prophetic values is still not optimal. The challenges faced in the implementation of prophetic leadership include limited conceptual understanding among managers, lack of formal training, and the lack of integration of prophetic coaching in the overall dormitory management system. Implications: This study emphasizes the importance of periodic training for dormitory managers and strengthening the prophetic value-based character development curriculum as a strategic step to increase the effectiveness of coaching in the UMKU dormitory environment. Novelty: this research lies in the systematic integration of the concept of prophetic leadership with the principle of servant leadership in the context of dormitory education, as well as in a comprehensive evaluation of the challenges and real impact of prophetic leadership on the formation of Islamic and academically superior student character.